Perceived parenting dimensions, personality and happiness in Singapore : an exploratory study on parents. - Koh, Hui Ting. (2009)
A great deal of research has been conducted using western samples to examine personality and perceived parenting dimensions mediating through a third variable as determinants of happiness. This report aims to examine the role of the four perceived parenting dimensions (paternal care, paternal control, maternal care and maternal control) and two personality traits (extraversion and neuroticism) as predictors of self-reported happiness in a group of parents with children between ages 13 to 21 in Singapore. 207 (101 fathers and 106 mothers) participants completed the self-designed questionnaire. The questionnaire includes questions on perceived parenting dimensions, personality and happiness level. Measuring instruments such as Big Five Inventory (John et al., 1991), Parental Bonding Instrument (Parker et al., 1979) and Subjective Happiness Scale (Lyubomirsky and Lepper, 1999) were modified to cater to this study. Hierarchical regression was employed to analyse the data. Regression showed that the four perceived parenting dimensions and the two personality traits are significant predictors of happiness. Although second stage regressions suggest that perceived parenting dimensions is a function of extraversion and neuroticism but a strong relationship could not be established. Therefore, it cannot be concluded that personality might not be a good mediating factor between happiness and perceived parenting dimensions.